Kajian Intertekstual Drama Mega-Mega Karya Arifin C. Noer dan Waiting For Godot Karya Samuel Beckett - Alin Ambarwati; Seli Mauludani; Siti Masitoh; Kurnia Dewi Nurfadilah; Irawan Syarifuddin Daher (VISA: Journal of Vision and Ideas, 2025)
The research focuses on an intertextual review of the play Mega-mega script by Arifin C. Noer and Waiting for Godot by Samuel Beckett. Interesting things that can be highlighted from the drama mega by Arifin C. Noer and Waiting for Godot by Samuel Beckett is a type of text that is absurd and there are parallel motives related to the rapture of urban community problems in waiting for a life change. The purpose of this research is to find out the structure of play script; and know relationship the intertextuality between the script of Arifin C. Noer's Mega-mega drama and Samuel Beckett's Waiting for Godot. This research uses content analysis methods using the technique of analysis of the fabric which includes three components, namely: 1. data reduction; 2.present data; and 3. Conclution drawing. Data collection methods are done with observation techniques. The collected data is analyzed using interexstual studies. The results showed that there are similarities and differences in the structure of the drama between Arifin C. Noer's mega-mega play script and Samuel Beckett's Waiting for Godot; and there is an intertextual relationship that is interrelated between the script of Arifin C. Noer's Mega-mega drama and Waiting for Godot by Samuel Beckett. The usefulness of this research is to gain an in-depth understanding of the structure of the manuscript text; and add to the treasure of knowledge about intertextual reviews between world and Indonesian drama scripts.